EVALUATION BY MEDICAL UNIVERSITY STUDENTS OF LEARNING USING DISTANCE EDUCATIONAL TECHNOLOGIES - Владимир Александрович Плаксин; Яна Александровна Русинова; Эдгар Артурович Мордовский; Елена Викторовна Шалаурова; Надежда Юрьевна Плаксина (Медицина в Кузбассе)
Distance learning technologies are understood as educational technologies implemented mainly with the use of information and telecommunication networks with the indirect interaction of students and teaching staff. The University organized the work of students and teachers in an electronic information and educational environment. A cross-sectional sociological survey was carried out by means of a questionnaire among students to assess the level of readiness and adaptability of students. The respondents indicated a significant amount of tasks and their complexity. It is noted that the teachers themselves did not have the proper skills to work remotely. The majority indicated a reduction in the volume of current academic debt in disciplines. The level of readiness of medical university students for this type of training is assessed as moderate and should be applied selectively.